2021
DOI: 10.1525/elementa.2021.00049
|View full text |Cite
|
Sign up to set email alerts
|

A global atlas of artificial light at night under the sea

Abstract: The impacts of artificial light at night (ALAN) on marine ecosystems have emerged as a focus for ecological light pollution research in recent years, yet the global prevalence of ALAN in underwater marine ecosystems is unknown. We have derived a global atlas of ALAN throughout the marine water column that will accelerate our understanding of its sources and environmental impacts. At a depth of 1 m, 1.9 million km2 of the world’s coastal seas are exposed to biologically important ALAN, which equates to around 3… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
17
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(17 citation statements)
references
References 48 publications
(86 reference statements)
0
17
0
Order By: Relevance
“…It is reported that between one tenth to one fifth of global land experiencing some degree of light pollution [30]. Additionally, almost seventy five percent of the seafloor adjacent to cities reported to be affected by artificial light at night to a level that could create negative biological responses for the animals living in that vicinity [31]. It is reported that aside from its negative effects on human wellbeing, artificial light at night shows disruptive effects on different land and water-based organisms while negatively impacting their natural circadian systems [32].…”
Section: Discussionmentioning
confidence: 99%
“…It is reported that between one tenth to one fifth of global land experiencing some degree of light pollution [30]. Additionally, almost seventy five percent of the seafloor adjacent to cities reported to be affected by artificial light at night to a level that could create negative biological responses for the animals living in that vicinity [31]. It is reported that aside from its negative effects on human wellbeing, artificial light at night shows disruptive effects on different land and water-based organisms while negatively impacting their natural circadian systems [32].…”
Section: Discussionmentioning
confidence: 99%
“…Those authors showed that in laboratory conditions ALAN (~ 200 lux) (Falchi et al, 2016) and sea surface irradiances (Davies et al, 2020), coupled with the monthly climatologies of globally inherent optical water properties and validated against in situ data collected from the Persian Gulf (Tamir et al, 2017). "Biologically important ALAN" is defined as the minimum irradiances of white light that elicit diel vertical migration in female Calanus copepods (Båtnes et al, 2013) [see Smyth et al, 2021 Bregazzi and Naylor (1972), A. longicornis was found to recover its natural rhythm of activity shortly after ALAN was removed from the system (Lynn, Flynn, et al, 2021). By contrast, Fanini et al (2016) found that the locomotor activity of the amphipod Platorchestia smithi was similar in a beach exposed to ALAN with respect to another that was not exposed.…”
Section: Introductionmentioning
confidence: 98%
“…The data is derived from the relationship between The New World Atlas of Artificial Night Sky Brightness (Falchi et al, 2016) and sea surface irradiances (Davies et al, 2020), coupled with the monthly climatologies of globally inherent optical water properties and validated against in situ data collected from the Persian Gulf (Tamir et al, 2017). “Biologically important ALAN” is defined as the minimum irradiances of white light that elicit diel vertical migration in female Calanus copepods (Båtnes et al, 2013) [see Smyth et al, 2021 for further details]. Maps are representative of average ALAN penetration over a typical year.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Human-produced light at night from electric light sources is often noted by the initialism ALAN, meaning anthropogenic light at night or artificial light at night. ALAN is increasing year over year [1,2], penetrates marine ecosystems [3], and is exacerbated by increasing market penetration of "blue-rich" LED sources producing consistent short wavelength radiation in the 400 -500 nm (violet-blue) range (see for example, [4]). As of 2018, LED outdoor lighting had an estimated penetration rate of 46 -50% [5], and it is estimated that the demand for per-capita light consumption has not been saturated [5,6].…”
Section: Introductionmentioning
confidence: 99%